2022
DOI: 10.1111/emip.12488
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Learning Progression Verification Method based on the Hierarchical Diagnostic Classification Model: Taking Grade 5 Students’ Fractional Operations as an Example

Abstract: Learning progressions can reflect students’ continuous in‐depth thinking development paths, and their establishment is an iterative process from the construction of hypothetical learning progressions to the verification of that hypotheses. Considering the limitations of the existing verification method of learning progressions based on a rule space model, this study put forward a new validating method based on the hierarchical diagnostic classification model (HDCM) and developed a learning progression with gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…That is, we do not assume any hierarchical or directional relationship among the attributes. However, as noted by Rupp et al (2010), the unstructured specification is unlikely to reflect observed data in educational contexts where hierarchical structures arise naturally (e.g., skills build on prerequisite skills)-for instance, when assessments are developed based on learning progressions, trajectories, or maps (e.g., Li et al, 2023;Yuan et al, 2022). As an example, Figure 2 shows a linear hierarchy where attribute 𝛼 𝐽 is mastered before 𝛼 𝐾 , which in turn must be mastered before 𝛼 𝐿 .…”
Section: Assessing Attribute Dependenciesmentioning
confidence: 99%
“…That is, we do not assume any hierarchical or directional relationship among the attributes. However, as noted by Rupp et al (2010), the unstructured specification is unlikely to reflect observed data in educational contexts where hierarchical structures arise naturally (e.g., skills build on prerequisite skills)-for instance, when assessments are developed based on learning progressions, trajectories, or maps (e.g., Li et al, 2023;Yuan et al, 2022). As an example, Figure 2 shows a linear hierarchy where attribute 𝛼 𝐽 is mastered before 𝛼 𝐾 , which in turn must be mastered before 𝛼 𝐿 .…”
Section: Assessing Attribute Dependenciesmentioning
confidence: 99%
“…Different methods are employed to validate LPs. Among these, the item response theory (IRT) model is widely used (Yuan et al, 2022). The use of IRT models assumes that a student's pattern of thinking regarding a particular concept can be mapped as a continuous latent knowledge structure and that a task difficulty provides information regarding progress in the LP.…”
Section: Evaluation Of the Learning Progressionmentioning
confidence: 99%